Sporadic multiprocessor Linux scheduler - Sousa, Paulo Baltarejo (2014)
The advent of multicore systems has renewed the interest of research community on real-time scheduling on multiprocessor systems. Real-time scheduling theory for uniprocessors is considered a mature research field, but real-time scheduling theory for multiprocessors is an emerging research field. Being part of this research community I have decided to implement the Sporadic Multiprocessor Linux Scheduler that implements a new real-time scheduling algorithm, which was designed to schedule real-time sporadic tasks on multiprocessor systems. This technical reports describes the implementation of the SMLS.